PENGEMBANGAN DESTINASI WISATA KEBUN RAYA CIBINONG SEBAGAI STRATEGI RESILIENSI - Vanny Chang Nurmanto; Rizki Nurul Nugraha (Media Bina Ilmiah, 2024)
This research aims to develop Cibinong Botanical Garden as a tourist destination using the 5A components (Attractions, Activities, Accommodation, Accessibility, Amenity) with a focus on resilience strategies in the face of change. The research approach is qualitative, with data collected through in-depth interviews, participatory observation and document analysis. This research identifies the potential and constraints faced in the current development of Cibinong Botanical Garden. Data analysis was conducted using Nvivo 12 pro software to identify key themes and patterns. The results showed that Cibinong Botanical Garden is facing quite heavy challenges, especially in the 5A component which is still far from perfect, such as limited transportation access, lack of attractions and lack of supporting facilities at Cibinong Botanical Garden due to limited funds due to low visits. Through qualitative descriptive analysis, that improving amenity, developing nature-based attractions and supporting services will be key strategies in strengthening the resilience and attractiveness of Cibinong Botanical Garden as a nature tourism destination. The implementation of this development plan is expected to increase tourist visits and support Cibinong Botanical Garden as a superior tourist destination in Bogor Regency.